A Two-stage Energy Extraction Circuit for Energy Harvesting in Non-Sinusoidal Excited Environments - Dorsch, Philipp; Bartsch, Toni; Hubert, Florian; Milosiu, Heinrich; Rupitsch, Stefan (Proceedings Eurosensors 2018, 2018)
We present a two-stage energy extraction circuit for a piezoelectric energy harvester, powering an asset-tracking system. Exploiting non-sinusoidal accelerations generated by many logistic transport devices, e.g., pushcarts, forklifts, assembly belts or cars, we are able to harvest sufficient electrical energy to transmit radio signals, which will allow to track the object when it is moving. By using the proposed energy extraction circuit, the energy extraction efficiency could be improved by at least 30% compared to a single-stage solution for sinusoidal excitations. In the practical use-case, the two-stage energy extraction network performs more than four times better compared to the single staged on.<br
Keywords: energy harvesting; piezoelectricity; energy extraction networks